Skema Citra dalam Lagu Go Go Yuureisen Karya Kenshi Yonezu: Kajian Linguistik Kognitif - Anisah, Siti; Aibonotika, Arza; Nasution, Yenny Aristia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research analyzes the use of metaphor in the song Go Go Yuureisen by Kenshi Yonezu using a cognitive linguistic approach. The main focus of the study is the identification and classification of conceptual metaphors based on Lakoff and Johnson's theory, as well as image schema analysis using Croft and Cruse's theory. The research results show that in song lyrics there are three types of conceptual metaphors, namely structural, orientational and ontological metaphors. In addition, seven image schemes were identified, namely power, container, color, space, connecting, part-whole, and existence schemes. In-depth analysis of several metaphors, such as “Love is also an endless sight” and “Little soldiers spin sounds,” reveals how human sensorimotor experiences are translated into abstract concepts through the relationship between the source domain and the target domain. For example, the journey schema is used to visualize love as a continuous process, while the agency and action schema depict creativity as an active struggle. This research highlights how metaphors and imagery schemes in songs can build a deep understanding of life experiences, emotions and human struggles, as well as offering insight into the artistic richness of language use. Keywords: Song, Image Scheme, Cognitive Linguistics